2023
DOI: 10.1186/s13052-023-01540-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pancreatic Stone Protein for diagnosis of sepsis in children admitted to pediatric intensive care or high-dependency care: a pilot study

Gabriella Bottari,
Mariangela Caruso,
Emanuel Paionni
et al.

Abstract: Background Pancreatic Stone Protein (PSP) is one of the most promising diagnostic and prognostic markers. The aim of the study was to assess the accuracy of PSP, compared to C-Reactive Protein (CRP), and Procalcitonin (PCT) for sepsis diagnosis in pediatric patients. Furthermore, we explored the correlation of PSP levels with sepsis severity and organ failure measured with PELOD-2 score. Methods Forty pediatric patients were enrolled following admi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Searching for clinical studies of PSP and infection or sepsis in PubMed, we identified 1 prospective multicenter study, 29 20 prospective observational studies (Table 3 and 4), 2 meta-analyses, 30,31 2 literature reviews, 32,33 1 economic study, 34 2 technology study, 35,36 1 case report, 37 3 Covid-19 studies, [38][39][40] 1 book chapter, 41 2 point-of-view articles. 42,43 From the PubMed citations, we excluded 8 children studies, [44][45][46][47][48][49][50][51] 3 neonate studies, [52][53][54] 1 post-mortem study, 55 1 study in women for pregnancy-related disease, 56 1 PSP and diabetes study, 57 2 study protocols, 58,59 1 letter, 60 1 editorial, 61 4 comments, [62][63][64][65] and 1 published erratum. 66…”
Section: Pancreatic Stone Protein Clinical Studies For Infection and ...mentioning
confidence: 99%
“…Searching for clinical studies of PSP and infection or sepsis in PubMed, we identified 1 prospective multicenter study, 29 20 prospective observational studies (Table 3 and 4), 2 meta-analyses, 30,31 2 literature reviews, 32,33 1 economic study, 34 2 technology study, 35,36 1 case report, 37 3 Covid-19 studies, [38][39][40] 1 book chapter, 41 2 point-of-view articles. 42,43 From the PubMed citations, we excluded 8 children studies, [44][45][46][47][48][49][50][51] 3 neonate studies, [52][53][54] 1 post-mortem study, 55 1 study in women for pregnancy-related disease, 56 1 PSP and diabetes study, 57 2 study protocols, 58,59 1 letter, 60 1 editorial, 61 4 comments, [62][63][64][65] and 1 published erratum. 66…”
Section: Pancreatic Stone Protein Clinical Studies For Infection and ...mentioning
confidence: 99%